Challenges and opportunities using mobile communication applications (MCAP) in an online learning environment - Hamid, Mohamad Ikmal; Khamzah, Nor Ahmad; Mohd Yunus, Alwi; Mohd Shoid, Mohd Shamsul; Seman @ Kamarulzaman, Mohd Ridwan (Journal of Islamic, Social, Economics and Development, 2026)
The unprecedented pivot from traditional face-to-face instruction to digital learning environments in Malaysia, accelerated by global disruptions, has unveiled a constellation of structural, pedagogical, and technological barriers impeding the efficacy of online education. Anchored in the Unified Theory of Acceptance and Use of Technology (UTAUT), this study critically examines the multifaceted inhibitors to online learning adoption, with particular attention to performance expectancy, effort expectancy, facilitating conditions, social influence, trust, and learner satisfaction. Through a comprehensive synthesis of recent literature, findings reveal that Malaysian students grapple with uncertainty regarding the pedagogical effectiveness of digital platforms, compounded by insufficient digital literacy and limited fluency with complex technological tools. Systemic infrastructural inequities, particularly in rural and underserved regions, further marginalize student access, while inconsistent instructional engagement undermines the cultivation of a digitally cohesive learning culture. Additionally, pervasive apprehensions surrounding data privacy, cybersecurity, and academic integrity erode institutional trust, whereas persistent technical glitches detract from user satisfaction and learning continuity. Addressing these challenges necessitates a multi-layered and inclusive approach emphasizing the enhancement of digital competencies, the fortification of infrastructure, and the fostering of digitally resilient pedagogical ecosystems. This review offers timely insights into the dynamics shaping the online learning landscape in Malaysia and provides strategic considerations for educational policymakers, institutional leaders, and digital learning practitioners seeking to navigate the evolving contours of higher education in the digital age.